2013
DOI: 10.12720/joams.1.1.43-49
|View full text |Cite
|
Sign up to set email alerts
|

Finding Their Way around: International Students’ Use of Information Sources

Abstract: There has been some research on the information behaviour of international students that is related to their academic issues (e.g. coursework and patterns of library use). However, little research has explored other non-academic issues (e.g. access health services and accommodation) of international student everyday life. This paper therefore explores the sources of information that international students rely on for academic and everyday living as well as the patterns students use in accessing these informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In addition, as indicated earlier, even when international students do seek out information online, they do tend to rely on tried and tested sources. Alzougool, Chang, Gomes & Berry (2013) found that due to accessibility, international students can continue to rely on home country sources for online information. If students are able to find the information they are looking for in 'home sources', they are likely to be satisfied with that despite any perceived risk of relevance or reliability.…”
Section: Profiles Of International Students As Information Seekersmentioning
confidence: 99%
“…In addition, as indicated earlier, even when international students do seek out information online, they do tend to rely on tried and tested sources. Alzougool, Chang, Gomes & Berry (2013) found that due to accessibility, international students can continue to rely on home country sources for online information. If students are able to find the information they are looking for in 'home sources', they are likely to be satisfied with that despite any perceived risk of relevance or reliability.…”
Section: Profiles Of International Students As Information Seekersmentioning
confidence: 99%
“…Pre-arrival preparation typically includes providing information about visas, housing, class registration, and health insurance along with students' admissions packets, as well as through existing online channels such as the international student section of a university's home page, or through social media platforms (Ammigan, 2019;Andrade, 2006;Yi, 2007). However, while presumably all universities provide this information, students may not necessarily utilize it or may receive information with varying degrees of credibility elsewhere (Alzougool et al, 2013), compounding incorrect assumptions, expectations, or misinformation (Chang et al, 2012). In the context of the COVID-19 pandemic, however, the half-life of pre-arrival information is increasingly short as policies continually shift as a function of the evolving and dynamic nature of the pandemic.…”
Section: Pre-host Country Arrivalmentioning
confidence: 99%
“…In Australia, several have mapped the information seeking of international students both before their arrival to Australian institutions and after matriculation (Alzougool et al, 2013;Chang and Gomez, 2016). These studies have found that while there are many available online and offline sources, in general, students look to a single source for their information.…”
Section: International Student Communicationsmentioning
confidence: 99%